Fabrication of Precise 304 Stainless Steel Calibration Block (AISI 304) - Razis, Shahrul Afiq; M Amin, Sri Yulis; Mohd Alamin Pardi,; Nurul ‘Ain Abdul Latif, (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Due to the high price of step wedge calibration block in market, we need to design and create a precision dual-purpose Standard Calibration Block from Stainless Steel 304 using both Computer Numerical Control (CNC) and Electrical Discharge Machine (EDM) machining techniques, to use the Ultrasonic Testing (UT) method to measure the thickness of the fabricated specimen and, to evaluate the specimen's electrical conductivity using Eddy-Current Testing (ET). In order to ensure excellent precision and adherence to industry standards, the calibration block must be carefully designed and produced as part of this project. Because the block serves two purposes, it may be thoroughly evaluated utilizing a variety of non-destructive testing techniques, which is UT and ET. The UT method analyses the ultrasonic wave's time-of-flight through the material to produce precise thickness estimations. While this is going on, the ET technique detects the specimen's conductivity by creating eddy currents and seeing how they react also to find the depth of penetration. This abstract concludes by the calibration block is thoroughly characterized by the combination of various methodologies, which makes it a useful tool for industrial applications demanding accurate measurement and material property evaluation. In non-destructive testing applications, the production of accurate 304 stainless steel calibration blocks—including step wedges and eddy-current calibration blocks—has a major beneficial influence on measurement accuracy, consistency, durability, traceability, and testing efficiency. In a number of industrial industries, these advancements help to increase cost-effectiveness, safety, and quality control. This research emphasizes how crucial non-destructive testing and modern manufacturing are to the creation of trustworthy calibration instruments.